2013
DOI: 10.1021/jf3043727
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, Antioxidant and Sensory Properties of Peach Wine Made from Redhaven Cultivar

Abstract: Physicochemical, sensory, and health-related characteristics of peach wine produced from Redhaven variety and selected white wines produced from various grape varieties were determined and compared. The alcohol content, titratable acidity, and total extract of peach wine was significantly lower compared with that of white wines, while its pH value was higher. The content of total phenolics (TPC) and flavonoids (TFC) of peach wine (402.53 mg/L GAE and 332.67 mg CAE/L, respectively) have been found significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 26 publications
1
29
1
Order By: Relevance
“…This widely celebrated alcoholic drink across the globe is primarily made from grapes but several other fruits and berries, including apple, pear, peach, blackberry, raspberry, strawberry, cherry, blueberry, plum, banana, and mango, are also being used. In many cases, additional supplements such as sucrose, honey, medicinal herbs, and local fruits are also practiced to make wines having higher medicinal value with characteristic flavor (Davidović et al., 2013; Jagtap & Bapat, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…This widely celebrated alcoholic drink across the globe is primarily made from grapes but several other fruits and berries, including apple, pear, peach, blackberry, raspberry, strawberry, cherry, blueberry, plum, banana, and mango, are also being used. In many cases, additional supplements such as sucrose, honey, medicinal herbs, and local fruits are also practiced to make wines having higher medicinal value with characteristic flavor (Davidović et al., 2013; Jagtap & Bapat, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…These results are in agreement with those available in the literature. [1] The redness (a*) of sample OMW rises significantly indicated that the over-maturity has a reinforcing effect on the redness of the honey peach wines, which may be related to the obvious oxidation and browning of peach juice during storage. [32] It has been found that when the ΔE* ≥ 2, the human eye can feel the difference in vision.…”
Section: Physicochemical Propertiesmentioning
confidence: 98%
“…[13] However, the TPC and TFC in 6 MW and 7-8 MW samples were still higher than white wine reported in other works of literature. [1] Davidovic's study concluded that peach wine is a better source of natural antioxidants than white wine. [1] Color and transmittance…”
Section: Physicochemical Propertiesmentioning
confidence: 99%
See 2 more Smart Citations